Evolving antimicrobial resistance in a patient receiving palliative OPAT for a vascular graft infection: A case report. (September 2019) - Irvine, James W.D.; Chapman, Ann L.N.; Lopez, Carlos Varon; Reid, Kerry; Spittal, Michelle; McCormick, Steven; Dundas, Stephanie
Abstract: Prosthetic vascular graft infection is devastating and frequently fatal. Cure requires removal of the graft and reperfusion by placement of a new graft. However, no evidence based guidelines exist for management where removal of the graft is not possible. We describe a patient who lived in a state of chronic infection suppression through outpatient parenteral antimicrobial therapy (OPAT) over a period of 32 months, and outline the challenges experienced and strategies used to suppress infection in the face of escalating antimicrobial resistance. To date there have been very few reports of OPAT used in the palliative context and this case illustrates the microbiological issues that can arise and the importance of the full OPAT multi-disciplinary team in managing these issues and optimising the patient's quality and length of life. Highlights: Cure of prosthetic vascular graft infections almost always requires removal and replacement of the graft Where this is not possible, long term antimicrobial suppression may maintain quality of life Outpatient parenteral antimicrobial therapy (OPAT) may be used for long term suppression where there are no oral antimicrobial options